2018
DOI: 10.1007/s11033-018-4294-5
|View full text |Cite
|
Sign up to set email alerts
|

A natural flavonoid lawsonaringenin induces cell cycle arrest and apoptosis in HT-29 colorectal cancer cells by targeting multiple signalling pathways

Abstract: Colorectal cancer is the third most common malignancy in the world having a high mortality rate. Flavonoids possess many biological activities including anti-cancer activity. lawsonaringenin (LSG) is a flavonoid isolated from leaves of Lawsonia alba Lam. The objective of this study was to demonstrate the anti-cancer potential of LSG in colorectal cancer for the first time. The HT-29 cells were treated with LSG or 5-fluoruracil, as a positive control, to determine its effect on cell cytotoxicity by a MTT cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Furthermore, apoptosis induced by senescence and oxidative stress in the ovary is bound to cause lower estrogen levels, thereby reducing the egg-laying performance of aged hens ( Manolagas, 2010 ). It is reported that flavonoids can increase the serum level of estrogen of old laying hen by alleviating the ovary apoptosis ( Anwar et al, 2018 ; Yang et al, 2018 ; Maues et al, 2019 ). The current study indicated that adding HF into the diet of aged breeder hens increased the serum levels of estrogen and alleviated the ovary apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, apoptosis induced by senescence and oxidative stress in the ovary is bound to cause lower estrogen levels, thereby reducing the egg-laying performance of aged hens ( Manolagas, 2010 ). It is reported that flavonoids can increase the serum level of estrogen of old laying hen by alleviating the ovary apoptosis ( Anwar et al, 2018 ; Yang et al, 2018 ; Maues et al, 2019 ). The current study indicated that adding HF into the diet of aged breeder hens increased the serum levels of estrogen and alleviated the ovary apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated both plant extracts were able to arrest the cell cycle at different phases (Figure 5). It is reported that flavonoids and phenols can arrest the cell cycle in different cancer cells [35][36][37]. The results indicated that both plant extracts under study can induce apoptosis as late apoptosis and arresting the cells in different cell cycle phases (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 81%
“…In the end, we obtained all 33 candidate components (Supplementary Table 1) (The structures of the compounds were derived from NCBI 9 ) of SBD. Thereinto, flavonoids compounds have been reported to demonstrate significant biologic activity including anti-inflammatory, inhibit tumor angiogenesis, and cell cycle arrest (Zhang L. et al, 2017; Anwar et al, 2018). Such as, apigenin (MOL001 OB = 33.6% DL = 0.25), baicalein (MOL070 0B = 44.6% DL = 0.21).…”
Section: Resultsmentioning
confidence: 99%